(3cJGH GdQDjI (B( (3QDjI GdHGQi Ld hYdG (B)s - (3GdOQGbWfj , CHh GdMSf,J (B385 (3g` s
(3ChdgG (B:s
(3gPG cJGH Mad LeYJ ajg eG hQO ef GdfUhU GdhGQOg ai cJGH Gddg JYGdi hCMGOjK GdfHi Udi Gddg Ydjg hSde GdeJYdbI HQDjI GdHGQi Ld hYdG hHYV CehQ GdBNQI s
(3BNQgG (B:s
(3Yf Ce GdWajd CeQCI CHj Hf cYH CfgG SeYJ QShd Gddg Udi Gddg Ydjg hSde jPcQ Cfg QCi QHg YR hLd ai CMSf UhQI TGHkG ehaQkG QLdGg ai Gd MVQ Ydjg fYdG ef PgH Ydi hLgI aQGT ef PgH BNQ GdQDjG Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3fSNI fajSI hYdjgG SeGYGJ cKjQI HYVgG efbhd Yf GdCUd GdefJSN Yfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B157s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1421s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs